Meso-scale numerical study of composite patch repaired hole drilled steel plate - Setvati, M.R. (Asian Research Publishing Network, 2016)
A large number of steel structures, such as bridges, offshore platforms, large mining equipment and buildings, need retrofitting 1. The use of composite materials patching is a very attractive alternative to the traditional reinforcement or repair methods (i.e. bolted doubler plates, welding), overcoming many of their limitations and disadvantages 2. In this paper numerical models of hole drilled steel plate without repair and composite patch repaired hole drilled steel plate were developed, analyzed and compared using ANSYS software. The hole acts as damage, such as severe localized corrosion, in the steel plate, resulting in the development of high stress concentrations. Stress and strain results of the damaged steel plate indicated that three-ply composite patch reduced the maximum equivalent (von-Mises) stress and maximum equivalent elastic strain of the damaged plate by approximately 17.7% and 19.5%, respectively. Analyzing strains, stresses and failure criteria of the composite laminate requires to model the single layers a composite design is built up by. This method is called meso-scale approach. It requires material properties and thicknesses for each layer of the design. Plywise stress and strain results of the composite patch repair revealed that maximum stress and strain took place in the center of the first ply. Â© 2006-2016 Asian Research Publishing Network (ARPN). All rights reserved.